Estimation of stability derivatives of a delta wing in hypersonic flow - Crasta, Asha; Baig, Maugal Ahmed Ali; Khan, Sher Afghan (RS Publication, 2012)
In the present study supersonic similitude has been used to obtain stability derivatives in pitch and roll of a delta wing for attached shock case. A strip theory is used in which strips at different span wise locations are independent. This combines with similitude to give a piston theory. The present theory is valid for attached shock case. Effects of wave reflections and viscosity have not been taken into account. Some of the results have been compared with those of Hui et. al. (1982), Ghosh (1984), and Liu & Hiu (1977). Results have been obtained for hypersonic flow of perfect case over a wide range of Mach number, incidences and sweep angles. A good agreement is obtained with Hui et al in some special cases.